2011
DOI: 10.1111/j.1467-9442.2011.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Public or Private Sector Wage Leadership? An International Perspective*

Abstract: Whether a government acts as a wage leader, placing pressure on private-sector wages (more open to competition), or whether it plays a passive role and merely follows wage negotiations in the private sector, there are important implications for macroeconomic development, particularly in small open economies and/or countries that are members of a monetary union, such as those of the European Monetary Union. With the notable exception of the case of Sweden, opinion on this issue is still divided. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 10 publications
1
48
0
Order By: Relevance
“…When testing it in the other direction, namely from manufacturing to general government compensations, it is found that the long-run elasticity of government with respect to manufacturing compensations is of 0.8%, thus much stronger than the 0.4% elasticity of manufacturing with respect to general government compensations. This confirms results from, for example, Lamo et al (2007Lamo et al ( ) (2012, where it is found that the private sector is more likely to have an impact on the public sector than vice versa, including in the long-run when covariates are accounted for. Secondly, in line with expectations, we find no difference between large and small government sectors; as a matter of fact, this dimension should be relevant only when it comes to assessing the impact of the public on the private traded sector.…”
Section: 1supporting
confidence: 77%
See 2 more Smart Citations
“…When testing it in the other direction, namely from manufacturing to general government compensations, it is found that the long-run elasticity of government with respect to manufacturing compensations is of 0.8%, thus much stronger than the 0.4% elasticity of manufacturing with respect to general government compensations. This confirms results from, for example, Lamo et al (2007Lamo et al ( ) (2012, where it is found that the private sector is more likely to have an impact on the public sector than vice versa, including in the long-run when covariates are accounted for. Secondly, in line with expectations, we find no difference between large and small government sectors; as a matter of fact, this dimension should be relevant only when it comes to assessing the impact of the public on the private traded sector.…”
Section: 1supporting
confidence: 77%
“…They find that the interaction goes both ways and that each 1% increase in real public sector wage growth raises private sector real wage growth by 0.3%. Lamo et al (2007Lamo et al ( , 2012Lamo et al ( , 2013 use different statistical techniques to analyse co-movement in the short-, medium-and long-term but include also a causality test. They find strong crosssectoral correlation between public and private wages, with coefficients as high as 0.8.…”
Section: The Public-private Wage Link In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of recent empirical papers provides evidence of a direct causal relationship between these variables (HolmHadulla et al, 2010;Pérez and Sánchez, 2011;Lamo, Pérez and Schuknecht, 2012). While private wages tend to lead public wages in the long-run, for some countries bi-directional causality (i.e.…”
Section: An Overviewmentioning
confidence: 99%
“…See for instance Alesina et al (2002), Afonso and Gomes (2008), Lamo, Pérez and Schuknecht (2012), Marzinotto and Turrini (2016) or Holm-Hadulla, et al (2010). 4 See, among others, Campos et al (2015).…”
mentioning
confidence: 99%